2018
DOI: 10.1111/mms.12505
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying variation in killer whale (Orcinus orca) morphology using elliptical Fourier analysis

Abstract: In the northeastern Pacific Ocean, there are three “ecotypes” of killer whales that differ in diet, ecology, behavior, acoustics, genetics, and morphology. Previous attempts to describe the morphological differences among populations of killer whales (Orcinus orca) have been limited to descriptive accounts or categorical studies. We used elliptical Fourier analysis (EFA) to quantify shape differences of dorsal fins and pigmentation patterns among the ecotypes from photo‐identification data of more than 500 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Greater agility and smaller body sizes may be advantageous in fish‐eating SRKWs, while BKWs may benefit from larger body sizes as they hunt larger and more formidable marine mammals. Phenotypic differences in the pigmentation of the saddle patch and eye patch regions and the shape of the dorsal fin (Baird & Stacey, 1988, Emmons et al, 2019) have previously been reported for these ecotypes. Similarly, genomic signatures of diet adaptation have been revealed between Resident and BKWs, notably relating to differences in digestive requirements for diets of different protein content (Foote et al, 2016).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Greater agility and smaller body sizes may be advantageous in fish‐eating SRKWs, while BKWs may benefit from larger body sizes as they hunt larger and more formidable marine mammals. Phenotypic differences in the pigmentation of the saddle patch and eye patch regions and the shape of the dorsal fin (Baird & Stacey, 1988, Emmons et al, 2019) have previously been reported for these ecotypes. Similarly, genomic signatures of diet adaptation have been revealed between Resident and BKWs, notably relating to differences in digestive requirements for diets of different protein content (Foote et al, 2016).…”
Section: Discussionmentioning
confidence: 88%
“…The HW/BHDF index was designed to quantify tissue loss in this region, and significant declines have been detected in emaciated SRKW individuals prior to death (Fearnbach et al, 2018). This measure is not as sensitive for detecting changes within individuals as the “eye patch ratio,” which measures the divergence of the white eyepatches of killer whales (Fearnbach et al, 2020), but Residents and BKWs are known to have small phenotypic variations in eye patch pigmentation that could impact the eye patch ratio (Emmons et al, 2019). The HW measure does not depend on pigmentation and has previously been used to compare killer whale ecotypes with known eye patch differences (Durban et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…A Procrustes fit was also required to align shapes. This method of alignment is often employed in studies that use elliptical Fourier analysis to quantify shapes with few major protrusions such as orca fins, human crania, and posterior lobes of Drosophila (Emmons et al, 2019;Friess & Baylac, 2003;Takahara & Takahashi, 2015).…”
Section: Elliptical Fourier Analysismentioning
confidence: 99%
“…Additionally, advancements in open-access software have facilitated a broader application of geometric morphometrics to photogrammetric, tomographic, and, even, standard photographs datasets (Baken et al, 2021;Emmons et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Reconstructive techniques, such as Fourier analysis (Lestrel, 1982; Rohlf, 1986), can be used in lieu of defining specific loci to approximate the entire pictograph as a series of sine and cosine waves. Additionally, advancements in open‐access software have facilitated a broader application of geometric morphometrics to photogrammetric, tomographic, and, even, standard photographs datasets (Baken et al, 2021; Emmons et al, 2019).…”
Section: Introductionmentioning
confidence: 99%